Ad-Dakhil dalam Surah Al-Anbiya’ Ayat 83-84 (Studi Kitab Tafsir Al-Khazin) - Nurul Hasanah; Ahmad Andi Agung; M. Ikhsan Iskandar Putra (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
This article discusses the element of ad-dakhil in the interpretation of surah al-Anbiya' verses 83-84 in the interpretation of al-Khazin, in which al-Khazin cites several stories of Israiliyat to corroborate its interpretation. In the science of interpretation, the existence of inauthentic sources such as the story of israiliyat, is something that needs to be studied more deeply so that the interpretation avoids the category of ad-dakhil. Thus, in this paper will be discussed about the biography of al-Khazin. the method and pattern of its interpretation, as well as the ad-dakhil elements such as what is contained in al-Khazin's interpretation in surah al-Anbiya' verses 83-84. Ad-dakhil in interpretation will certainly affect the meaning and understanding of the interpreted verse, so that interpretations containing elements of ad-dakhil can be categorized as flawed interpretations. The results of the study in this article reveal that in interpreting surah al-Anbiya' verses 83-84, al-Khazin included the story of israilyat whose story is unclear. In addition, the israiliyat story about the Prophet Job can be said to be a false story or a disability (ad-dakhil), because the story is not in line with Islamic law and previous interpretations, so this kind of israiliyat story will have an impact on the weakness of a person's aqidah